Breath holding index in episodic primary headaches - Podgorac, Ana; Petrušić, Igor; Radojičić, Aleksandra; Zidverc-Trajković, Jasna (Vojnosanitetski pregled, 2020)
Background/Aim. Examination of cerebrovascular reactivity in patients with primary headaches is focused mainly on migraine, while the smaller number of studies deals with tension-type and cluster headache, or comparison of cerebral haemodynamic in migraine and tension-type headache (TTH). In this study, we hypothesized that cerebrovascular reactivity differs among different types of episodic primary headaches. In order to prove that we aimed to compare the interictal cerebrovascular reactivity in patients with the episodic form of the three most common types of primary headaches using the breath holding test. Methods. Examination was performed in 243 patients, 100 migraineurs with aura (group I), 70 migraineurs without aura (group II), 38 patients with episodic tension-type headache (group III), 35 patients with episodic form of cluster headache (group IV) and 35 healthy controls (group V). The Doppler instrument was used for transcranial doppler (TCD) sonography and breath-holding test performance. Blood flow mean velocities (MV), pulsatility indices (PI) and breath-holding index (BHI) for middle cerebral artery among these groups were analyzed. Results. The mean velocities and pulsatility indices were not different in 4 groups of headache patients and controls. The BHI was found to be significantly greater in the migraineurs with aura (1.668 ± 0.269) compared with the patients with migraineurs without aura (1.411 ± 0.358, p = 0.005), tension type headache (1.401 ± 0.428, p = 0.035), cluster headache (1.203 ± 0.311, p < 0.01) and controls (1.195 ± 0.269, p < 0.01) showing an exaggerated reactivity to hypercapnia in patients with migraine with aura. Conclusion. In conclusion, our finding support the literature data that increased cerebrovascular reactivity is a feature of migraine with aura. Result of unchanged cerebrovascular reactivity in migraine without aura, cluster headache and tension-type headache is expected, still, it is possible that in future, using different technique, we will be able to put more light on vascular changes that are following different headache disorders.